Ethics and Communication in Providing Health Education in Midwifery Services - sari, Lili Purnama; Uliarta Marbun; Irnawati Irnawati; Arisna Kadir; Dahniar Dahniar (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: The aim was to analyze the differences in providing modules and assistance from a certified senior midwife in applying ethics and communication in providing health education in midwifery services. METHODOLOGY: This quantitative research used cluster sampling and was conducted in Makassar, Maros, Pangkep, and Barru cities between January and April 2024. Slovin formula and cluster sampling were used. Each region was divided into 30 samples, with a total sample size of 120. The midwife group was split into a control group that was given a health ethics and communication module (This module is developed based on the curriculum and combined with existing regulations from the Ministry of Health). The intervention group was provided with assistance from a certified senior midwife. Eight midwives from the control and intervention groups were randomly assigned to four cities, and an independent t-test was conducted to compare the control and intervention groups. SPSS was used for analytical tools. RESULTS: The findings show that age, education, and employment are all related to ethics and communication, with a p-value of <0.005 in both the control and intervention groups. The control and intervention groups showed significant differences in ethics and communication, with a p-value of 0.000 for both. CONCLUSION: Communication and ethics differences exist between the control and intervention groups. The findings emphasize how crucial it is to implement assistance from a certified senior midwife to enhance the quality of ethics and communication among these groups.